p-adic L-functions and Selmer varieties associated to elliptic curves with complex multiplication - Kim, M (Princeton University, Department of Mathematics, 2010)
We show how the finiteness of integral points on an elliptic curve over Q with complex multiplication can be accounted for by the nonvanishing of L-functions that leads to bounds for dimensions of Selmer varieties.